KOMBINASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS DAN SIKAP KOLABORATIF SISWA KELAS IV SD - Layli Norhayati; Nuhyal Ulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on the learning model of the combination of Problem Based Learning and Talking Stick learning models in improving students' understanding of mathematical concepts and collaborative attitudes. The purpose of this study was to determine the effect of the combination of Problem Based Learning and Talking Stick learning models on understanding mathematical concepts, and to determine the effect of collaborative attitudes on the combination of Problem Based Learning and Talking Stick learning models on understanding mathematical concepts. The research method used was quantitative. Data collection techniques used were tests and questionnaires. A descriptive test sheet of 8 questions to measure understanding of mathematical concepts and a questionnaire sheet of 10 statements to measure collaborative attitudes. The data analysis technique used a prerequisite test, namely the normality test and hypothesis data analysis, namely the paired t-test, gain test (N-gain) and linear regression test. The results of the paired t-test obtained sig. of = 0.000, can be written as 0.000 <0.05, then H0 is rejected, H1 is accepted. So, there is a significant difference in learning achievement between before and after using the combination of Problem Based Learning and Talking Stick learning models. The result of the N-gain test is 0.660 which shows an increase in the moderate criteria. The result of the collaborative attitude regression test is significant with the linear regression equation being Ŷ = 2.635 + 0.937 x and with a large influence of 30.5%.